Qadaya tibbiyah mu'asirah fi daw' al-shari'ah al-Islamiyah - (3LeYjI GdYdhe GdWHjI GdESdGejI (B((3LhQOGf(B)s (Amman : Dar al-Bashir, 2006)
Contemporery medical issues in the light of Islamic law
jilid 2. (3GdGSJfSGN, GdgfOSI GdhQGKjI, GNJjGQ LfS GdLfjf (B-s jilid 3. (3eYGde aj CNdGbjGJ GdegfI GdWHjI GNJdGdGJ CfeGW GdMjGIs
Keywords: Medical jurisprudence (Islamic law); Medical laws and legislation (Islamic law); Medicine -- Religious aspects -- Islam; Medical ethics